2016
DOI: 10.1177/1039856216646233
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry training experiences: a narrative synthesis

Abstract: There is a need to better understand how the junior doctor and medical student psychiatry experience influences perceptions of psychiatry and intention to specialise, especially in the Australian context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Many studies have examined student attitudes towards psychiatry. 1,2 These have been measured through scales such as the Attitudes Towards Psychiatry scale (ATP-30), 3 which assesses themes of patients, institutions, pathologies, treatment modalities, teaching and knowledge base. Such scores are remarkably globally consistent, and replication studies have reached saturation point.…”
mentioning
confidence: 99%
“…Many studies have examined student attitudes towards psychiatry. 1,2 These have been measured through scales such as the Attitudes Towards Psychiatry scale (ATP-30), 3 which assesses themes of patients, institutions, pathologies, treatment modalities, teaching and knowledge base. Such scores are remarkably globally consistent, and replication studies have reached saturation point.…”
mentioning
confidence: 99%
“…This theme supports other research which has found witnessing patient recovery as one of the most positive experiences of a psychiatry placement. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the ways in which residents and medical students experience psychiatry training is different than in other specialties, which may extend to experiences of IHD during training. [68][69][70] However, the available literature exploring the nature of the learning and training environment in psychiatry is controversial, with one study suggesting that perceptions and personal experiences of IHD within the psychiatric learning environment are low. 71 Previous studies have consistently demonstrated elevated rates of IHD among psychiatry trainees relative to other trainee groups.…”
Section: Ihd Among Psychiatry Residentsmentioning
confidence: 99%
“…75 Factors related to compassion fatigue and burnout may also be more common among psychiatry trainees given the empathic demands of their work and vicarious exposure to IHD. 69 Psychiatrists are also paid the least among medical specialties-a systematic factor that is outside of the immediate control of most physicians. [76][77][78] As IHD is considered a major risk factor for burnout, with a 2016 national survey of Canadian psychiatry residents finding that 21% reported symptoms of burnout, IHD encounters appear to play a critical role in psychiatry resident experiences of burnout.…”
Section: Ihd Among Psychiatry Residentsmentioning
confidence: 99%